2009
DOI: 10.1002/gcc.20683
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent chromosomal rearrangements implicate oncogenes contributing to T‐cell lymphomagenesis in Lck‐MyrAkt2 transgenic mice

Abstract: The oncogene v-akt was isolated from a retrovirus that induced naturally occurring thymic lymphomas in AKR mice. We hypothesized that constitutive activation of Akt2 could serve as a first hit for the clonal expansion of malignant T-cells by promoting cell survival and genomic instability, leading to chromosome alterations. Furthermore, genes that cooperate with Akt2 to promote malignant transformation may reside at translocation/inversion junctions found in spontaneous thymic lymphomas from transgenic mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 39 publications
(61 reference statements)
1
25
0
Order By: Relevance
“…21 The MyrAkt2 Tg model was selected because the most frequently observed mutations in T-ALL (ie, Notch activation or PTEN loss) activate AKT. 11,22 Non-Tg mice did not develop disease during the time of the study; however, MyrAkt2;Rpl22 ϩ/ϩ mice developed thymic lymphoma with a median latency of 19 weeks (Figure 2A).…”
Section: Rpl22 Haploinsufficiency Accelerates the Development Of T Lymentioning
confidence: 99%
“…21 The MyrAkt2 Tg model was selected because the most frequently observed mutations in T-ALL (ie, Notch activation or PTEN loss) activate AKT. 11,22 Non-Tg mice did not develop disease during the time of the study; however, MyrAkt2;Rpl22 ϩ/ϩ mice developed thymic lymphoma with a median latency of 19 weeks (Figure 2A).…”
Section: Rpl22 Haploinsufficiency Accelerates the Development Of T Lymentioning
confidence: 99%
“…The Lck-MyrAkt2 transgenic mice develop spontaneous, aggressive thymic lymphomas within 10–20 wks (7-9), with the added advantage that the mutant transgene bypasses the need for activation of phosphoinositides 3,4,5-trisphosphate (PIP 3 ) and PIP 2 generated by PI3K and, thus, cannot be inhibited by Pten. The Lck-MyrAkt2 model exhibits recurrent chromosomal rearrangements that result in overexpression of c-Myc, which is frequently observed in human lymphomas and postulated to cooperate with activated Akt to drive tumor formation (10, 11). …”
Section: Introductionmentioning
confidence: 99%
“…Lck-Myr (myristoylated)-Akt2, drives thymic T-cell lymphoma within 12-24 weeks in an Akt dosagedependent manner. 2 In some Lck-Myr-Akt2 founder lines, a recurrent chromosomal inversion implicated the homeobox gene Dlx5 as an oncogene. 3 In subsequent work (manuscript in preparation), we found that transgenic Lck-Dlx5 mice develop spontaneous thymic lymphomas that acquire constitutive activation of Akt, due to loss of Pten expression, as well as up regulation of Myc.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a mouse model of human T-ALL, expression of a constitutively active form of Akt2 specifically in immature T cells is sufficient to drive T-cell lymphoma formation. 2 Tumors from these transgenic mice consistently harbor one or the other of 2 recurrent chromosomal rearrangements that each involve somatic juxtaposition of a T cell receptor (TCR) enhancer and a transcription factor gene, either Dlx5 or Myc -in each case resulting in unregulated expression of Myc protein. 3 Myc is thought to be essential to T cell development, and Myc-null T cells fail to proliferate at the CD4/CD8 double-negative stage in mice.…”
Section: Introductionmentioning
confidence: 99%